2017
DOI: 10.1016/j.ajog.2016.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypertension is associated with increased risk of type 2 diabetes in adult offspring: the Helsinki Birth Cohort Study

Abstract: Background-Women with hypertensive disorders in pregnancy are at an increased risk of cardiovascular disease and type 2 diabetes later in life. Offspring born from these hypertensive pregnancies have increased levels of cardiovascular risk factors; whether they are at an increased risk of type 2 diabetes is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 12 publications
2
49
0
2
Order By: Relevance
“…These include infants exposed to maternal pre‐eclampsia. In a subset of the 1934–44 cohort, we previously reported that stroke was predicted by maternal pre‐eclampsia, which was present in 7.8% of those born preterm and 4.5% of those born at term. Should they have been born today, many more would have undergone medically indicated preterm delivery, which could have contributed to increased risk of stroke among those born preterm.…”
Section: Commentmentioning
confidence: 99%
“…These include infants exposed to maternal pre‐eclampsia. In a subset of the 1934–44 cohort, we previously reported that stroke was predicted by maternal pre‐eclampsia, which was present in 7.8% of those born preterm and 4.5% of those born at term. Should they have been born today, many more would have undergone medically indicated preterm delivery, which could have contributed to increased risk of stroke among those born preterm.…”
Section: Commentmentioning
confidence: 99%
“…[2][3][4] HDP have been associated with adverse health outcomes for both mothers and children, including subsequent hypertension and chronic kidney disease for mothers, 5,6 childhood overweight/obesity, type 2 diabetes and attention deficit/hyperactivity disorder (ADHD). [7][8][9] Therefore, it is important to identify the risk factors associated with HDP during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…This susceptibility to cardiorenal and metabolic diseases post–index pregnancy has been attributed to the pathophysiological mechanisms10, 11 initiated by the placental ischemia. In addition to the maternal effects, preeclampsia is highly associated with intrauterine growth restriction12 and developmentally programs the increased risk for cardiovascular disease,13, 14 stroke,15 renal disease,16 and metabolic dysfunction17, 18 in the adult offspring of preeclamptic women 19. Since the resolution of preeclampsia is achieved only through parturition of the ischemic placenta,20 a difficult decision often must be made between inducing early delivery in order to halt the progression of the syndrome in the mother and risking premature birth complications to the fetus 21.…”
mentioning
confidence: 99%